Number 45 (April 2003) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 2003)
(April 2003) - An Annotated List of Fishes Known from the Dan River in Virginia and North Carolina (Blue Ridge/Piedmont Provinces). By Fred C. Rohde, Rudolf G. Arndt, David J. Coughlan, and Scott M. Smith Minutes, Business Meeting, 28th Annual Meeting, Southeastern Fishes Council Regional Southeastern Fishes Council Reports
Keywords: fishes; dan river; virginia